2021
DOI: 10.1016/j.ajic.2020.11.023
|View full text |Cite
|
Sign up to set email alerts
|

Readability, content, and quality of COVID-19 patient education materials from academic medical centers in the United States

Abstract: Highlights COVID-19 PEMs are readily available on US academic medical websites. Content of COVID-19 PEMs is highly variable. PEMs on COVID-19 are written above the recommended sixth grade reading level. PEMs on COVID-19 are critical to disseminate accurate information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
28
2
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 29 publications
5
28
2
3
Order By: Relevance
“…Numerous studies have utilized PEMAT to measure understandability and actionability in educational material. 11,17,[23][24][25][26][27][28][29] At its conception, Shoemaker et al deemed that a score of 70% would signify an acceptably understandable or actionable POEM. The present study detected a mean understandability score of 52.8%.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have utilized PEMAT to measure understandability and actionability in educational material. 11,17,[23][24][25][26][27][28][29] At its conception, Shoemaker et al deemed that a score of 70% would signify an acceptably understandable or actionable POEM. The present study detected a mean understandability score of 52.8%.…”
Section: Discussionmentioning
confidence: 99%
“…Halboub et al [ 53 ] investigated 36 Arabic-language websites on COVID-19 and reported that 66.7% of the included websites were easy for the general public to read. Kruse et al [ 33 ] conducted a study of COVID-19 information provided by 8 US academic medical centers and reported that 0.7% of information was written at or below the sixth-grade level.…”
Section: Discussionmentioning
confidence: 99%
“…Documents were formatted as raw text files using Notepad (Microsoft Inc). Any text not directly related to public education was deleted, such as date, author information, titles, figures, tables, legends, references, and copyright information [ 31 , 33 , 36 ].…”
Section: Methodsmentioning
confidence: 99%
“…This was a somewhat unexpected result, given that websites that fall under the treatment/therapy/medical category aim to provide health information to a wide audience. However, previous literature has shown that hospital websites tend to have decreased readability, which can make them difficult for individuals to understand [ 32 , 33 ]. Hence, it is extremely important that healthcare providers spend time with their patients to educate them on the importance of these features in making informed decisions regarding their health.…”
Section: Discussionmentioning
confidence: 99%